Liver Cancer Neuroscience: Regulating Liver Tumors via Selective Hepatic Vagotomy - Kylynda C. Bauer; Shadin Ghabra; Chi Ma; Lee Chedester; Tim F. Greten (Methods and Protocols)
Both the prevalence and mortality of liver cancers continue to rise. Early surgical interventions, including liver transplantation or resection, remain the only curative treatment. Nerves in the periphery influence tumor growth within visceral organs. Emerging cancer neuroscience efforts linked parasympathetic vagus nerves with tumor pathology, underscoring the value of vagal nerve denervation methods within cancer mouse models. Here, we describe a selective hepatic vagotomy that largely maintains non-liver parasympathetic innervation in mice. To address vagal interactions in hepatic tumor pathology, we provide an adapted methodology utilizing an established liver metastatic model. We anticipate that this methodology will expand the burgeoning field of cancer neuroscience, enabling the study of the neuroimmune, neurometabolic, and/or nerve–microbiota interactions shaping liver cancer progression and treatment.